Parental divorce in childhood does not independently predict maternal depressive symptoms during pregnancy - Elviira Porthan; Matti Lindberg; Eeva Ekholm; Noora M. Scheinin; Linnea Karlsson; Hasse Karlsson; Juho Härkönen (BioMed Central (BMC), 2022)
Background: This study sought to investigate if parental divorce in childhood increases the risk for depressive symptoms in pregnancy.
Methods: Women were recruited during their ultrasound screening in gestational week (gwk) 12. The final study sample consisted of 2,899 pregnant women. Questionnaires (including the Edinburgh Postnatal Depression Scale) were completed at three measurement points (gwk 14, 24 and 34). Prenatal depressive symptoms were defined as Edinburgh Postnatal Depression Scale score ≥ 13. Parental divorce and other stressful life events in childhood were assessed at gwk 14. Parental divorce was defined as separation of parents who were married or cohabiting. Questionnaire data was supplemented with data from Statistics Finland and the Finnish Medical Birth Register.
Results: Parental divorce in childhood increased the risk for depressive symptoms during pregnancy (OR 1.47; 95% CI 1.02–2.13), but the connection was no longer significant after adjusting for socioeconomic status, family conflicts and witnessing domestic violence in the childhood family (OR 0.80; 95% CI 0.54–1.18).
Conclusions: Parental divorce alone does not predict depressive symptoms during pregnancy.
Keywords: prenatal depression, depression, parental divorce, family conflicts, domestic violence